ChemInform Abstract: Nocapyrones H—J, 3, 6‐Disubstituted α‐Pyrones from the Marine Actinomycete Nocardiopsis sp. KMF‐001. Issue 42 (1st October 2013) - Kim, Min Cheol; Kwon, Oh‐Wook; Park, Jin‐Soo; Kim, Sun Yeou; Kwon, Hak Cheol
Abstract Nocapyrone H (Ia) reduces the pro‐inflammatory factor and shows stronger inhibitory effect on NO production than chrysin in lipopolysaccharide‐stimulated BV‐2 microglial cells.